Beyond regulatory compression: confronting the liminal spaces of health research regulation. Issue 2 (6th December 2016) - Taylor-Alexander, Samuel; Dove, Edward S.; Fletcher, Isabel; Ganguli Mitra, Agomoni; McMillan, Catriona; Laurie, Graeme
ABSTRACT: Biomedicine and the life sciences continuously rearrange the relationship between culture and biology. In consequence, we increasingly look for a suitable regulatory response to reduce perceived uncertainty and instability. This article examines the full implications of this 'regulatory turn' by drawing on the anthropological concept of liminality. We offer the term 'regulatory compression' to characterise the effects of extant regulatory approaches on health research practices. With its focus on transformation and the 'in-between', liminality allows us to see how regulatory frameworks rely on a silo-based approach to classifying and regulating research objects such that they: (1) limit the flexibility necessary in clinical and laboratory research; (2) result in the emergence of unregulated spaces that lie between the bounded regulatory spheres; and (3) curtail modes of public participation in the health research enterprise. We suggest there is a need to develop the notion of 'processual regulation', a novel framework that requires a temporal-spatial examination of regulatory spaces and practices as these are experienced by all actors, including the relationship of actors with the objects of regulation.